VOCABULARY IN TEACHING TURKISH AS A FOREIGN LANGUAGE - Faruk ÖZTÜRK (Fırat University, 2019)
Although there are vocabulary studies in teaching Turkish as a native language in Turkey, vocabulary studies in teaching Turkish as a foreign language are insufficient. And, this situation shows that there is an urgent need for vocabulary studies in teaching Turkish as a foreign language. However, what kind of a design will be used, which frames and which ways will be determined, and what kinds of conditions and environments will be needed for the detection studies of vocabulary constitute big problems. While the studies are implemented on the data which were collected from written language in the detection studies of vocabulary in teaching Turkish as a native language, it is a different issue which data should be studied in the detection studies of vocabulary in teaching Turkish as a foreign language. A sufficient and wide scale study on which words should be taught for which level and how these words will be formed in teaching Turkish as a foreign language have not been determined. Despite the fact that there is a long history of teaching Turkish as a foreign language, still its lacks and inefficiencies known to be exist. Thereby, in teaching Turkish as a foreign language situation analysis must be done not only in program and material development subject but also in vocabulary matters.The motive behind this study is to show the vocabulary in teaching Turkish to foreigners, and to show how vocabulary learning can be developed effectively. The motive behind this study is to show the vocabulary in teaching Turkish to foreigners, and to show how vocabulary learning can be developed effectively. 75 boys and 120 girls learning Turkish as a Foreign Language (TFL) at KTMU took part as a treatment group in this research study. The participants are from six different countries (Kyrgyzstan, Kazakhstan, Uzbekistan, Turkmenistan, Afghanistan, and Tajikistan) and 12 different nationalities (Kyrgyz, Kazakhstani, Uzbek, Russian, German, Tadzhik, Chechen, Uighur, Azerbaijani, Afghan, Turkish, Tadzhik).